Autism Spectrum Disorder and Amplified Pain - Ciaran Clarke (Case Reports in Psychiatry)
Among the core features of ASD, altered sensitivities in all modalities have been accorded increasing importance. Heightened sensitivity to pain and unusual expressions of and reaction to pain have not hitherto been widely recognised as a presenting feature of ASD in general paediatrics. Failure to recognise ASD as a common cause of pain can lead to late diagnosis, inappropriate treatment, distress, and further disability. Two cases are presented which illustrate the late presentation of Autism Spectrum Disorder (Asperger’s Syndrome subtype) with chronic unusual pain. Conclusion. Pain in autism can be atypical in its experience and expression and for this reason may go unrecognised by physicians treating chronic pain disorders.